Pengaruh Person Job Fit (Pj-Fit) dan Pendidikan Terhadap Kinerja Karyawan pada PT. Citra Putra Kebun Asri (CPKA) - Jaya, Fanlia Prima; Sulaiman, Sulaiman; Rusvitawati, Devi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2019)
The study was conducted to explore the relationship of Person Job Fit (PJ-Fit), and Pendidikan on Kinerja Karyawan on PT. Citra Putra Kebun Asri (CPKA). The populatian of this study is 477 employees of PT. Citra Puta Kebun Asri (CPKA). In order to determine the sample, this study used Slovin Formula. The questionnaires were distributed to 83 sample respondents. The data were analyzed by using SPSS Software Version 19.0 and Linear Regression. The result showed that Person Job Fit (PJ-Fit) and Education has a significant on Employee Performance.